2001
DOI: 10.1253/jcj.65.572
|View full text |Cite
|
Sign up to set email alerts
|

Large Thrombus in the Ascending Aorta Successfully Treated by Thrombolysis

Abstract: cute myocardial infarction (AMI) is confirmed by angiographic evidence of coronary artery occlusion, which is usually caused by a thrombus or by atherosclerosis. 1 A thrombus located close to the orifice of the coronary artery in the ascending aorta in connection with AMI is rare, 2,3 but we report such a case and discuss the thrombogenetic role of risk factors and the therapeutic strategy of thrombolysis. Case ReportA 52-year-old woman complained of chest pain in the morning of 13 September 1993 and was trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 8 publications
1
33
0
1
Order By: Relevance
“…3,[5][6][7] We provided definitive echographic evidence that a mobile mass provoked intermittent left coronary occlusion. Ito et al reported the use of thrombolytic therapy for fresh thrombus in the ascending aorta, 4 but we did not consider the mass to be fresh thrombus on the basis of TEE findings and thus surgical treatment was employed. Our experience suggests TEE is particularly useful for showing not only the anatomical structure but also its characteristics when a thrombus or tumor is suspected in the sinus of Valsalva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,[5][6][7] We provided definitive echographic evidence that a mobile mass provoked intermittent left coronary occlusion. Ito et al reported the use of thrombolytic therapy for fresh thrombus in the ascending aorta, 4 but we did not consider the mass to be fresh thrombus on the basis of TEE findings and thus surgical treatment was employed. Our experience suggests TEE is particularly useful for showing not only the anatomical structure but also its characteristics when a thrombus or tumor is suspected in the sinus of Valsalva.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis in the ascending aorta [2][3][4][5] or in the sinus of Valsalva 6,7 associated with AMI is a very rare condition. As much as 150 years ago, Rudolf Virchow pointed out 3 important factors necessary for thrombus formation; namely, abnormalities in blood flow, blood constituents, and the vessel wall, which are now referred to as Virchow's triad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an aortic mural thrombus in a non-aneurysmal mildly atherosclerotic or normal aorta is a very rare clinical entity [1,3]. Therefore, with respect to the primary management for this unusual problem, many physicians are at a loss which to choose [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Both anticoagulation therapy (including thrombolysis) and aortic surgery are commonly used as primary treatment [2][3][4][5]8], but there is no consensus. The results of the literature described above [1] showed that mortality rates were similar between groups; however, patients who received anticoagulation medication as primary therapy tended to have more complications such as stroke, limb loss, and bowel resection.…”
Section: Discussionmentioning
confidence: 99%